2006
DOI: 10.1111/j.1467-9515.2006.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Means Testing and the Heterogeneity of Housing Assets: Funding Long-Term Care in Spain

Abstract: The access to publicly funded long-term care (LTC) in Spain has been traditionally rationed through the use of means tests based on individuals' current income and needs. However, individuals' wealth, primarily housing assets, is progressively taken into account. Parallel to this feature, the responsibilities for the organization of LTC services have been devolved to region-states -autonomous communities (ACs), giving rise to some regional heterogeneity, though limited evidence has been reported on the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, proponents of devolution argue that as a governance model it can give rise to competition (or cooperation) among regional governments and spill‐over effects, especially when a neighbouring government's performance is taken as a yardstick to evaluate regional welfare policy (Salmon 1987). Devolution also responds best to local preferences when heterogeneity in regional preferences makes the ‘strategy of equality’ (or uniformity) socially undesirable (Costa‐Font et al . 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, proponents of devolution argue that as a governance model it can give rise to competition (or cooperation) among regional governments and spill‐over effects, especially when a neighbouring government's performance is taken as a yardstick to evaluate regional welfare policy (Salmon 1987). Devolution also responds best to local preferences when heterogeneity in regional preferences makes the ‘strategy of equality’ (or uniformity) socially undesirable (Costa‐Font et al . 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, although housing can act as a self-insurance mechanism in old age, liquidity problems arise when long-term care (LTC) has to be paid for out of individual wealth. Yet, in countries such as Spain where the family still plays a key role (unlike in other central and northern European countries where financial independence is a key value) housing wealth is the main asset protecting the family in those areas where social protection is not universal, such as LTC services (Costa-Font et al, 2006).…”
mentioning
confidence: 99%
“…For large parts of the older population, a major part of accumulated wealth consists of owning the residence where they live. The obligation to spend down wealth to finance LTC services may or may not include housing, but housing wealth is increasingly being included (Costa-Font et al, 2006). For the United States, it was found that housing wealth of nursing home entrants fell steadily over a six-year period, resulting in a median housing wealth of zero within six years after the initial nursing home entry (Banerjee, 2012).…”
Section: Social Ltc Insurancementioning
confidence: 99%